Anita de Monte laughs last [large type] - Gonzalez, Xochitl, 1977- (Reese's book club., 2024)
"1985. Anita de Monte, a rising star in the art world, is found dead in New York City. By 1998 Anita's name has been all but forgotten--certainly by the time Raquel, a third-year art history student is preparing her final thesis. On College Hill, surrounded by privileged students who futures are already paved out for them, Raquel feels like an outsider. But when she becomes romantically involved with a well-connected older art student, she finds herself rising up the social ranks. As she attempts to straddle both worlds, she stumbles upon Anita's story, raising questions about the dynamics of her own relationship, which eerily mirrors that of the forgotten artist"--